Synthesis of an adaptive control system for municipal outdoor lighting based on multicriteria optimization - Plyeskov, P.; Zinzura, V.; Petrova, K.; Soldatenko, V.; Pavlenko, V. (Energy and Automation, 2026)
The paper addresses the urgent problem of increasing energy efficiency in municipal outdoor lighting systems, which often operate with excessive power margins. The study aims to enhance the energy efficiency and operational quality of street lighting systems by improving a control system that accounts for natural light levels, luminous flux uniformity indicators, and equipment service life.A mathematical model of the spatial light field distribution has been developed, and the automatic lighting level control problem is formulated as a multi-objective optimization task. To find a compromise solution between minimizing energy consumption and maximizing both lighting uniformity and equipment resource, the method of approaching the "ideal (utopian) point" in the criteria space using the Chebyshev metric was applied.Numerical simulation for a typical highway section confirmed the effectiveness of the proposed approach. It was established that the adaptive system provides a reduction in power consumption by 27.9% (from 600 W to 432.6 W) compared to traditional timer-based systems. Savings are achieved by compensating for the natural background and eliminating the technological lighting margin — reducing the minimum level from 20.02 lx to the standardized 15.00 lx. Simultaneously, longitudinal uniformity is increased from 0.778 to 0.790, and the predicted service life of the luminaires is nearly doubled (up to 100,000 hours) due to reduced thermal load.The implementation of this method enables the creation of Smart City class systems that adapt to real-world visibility conditions, guaranteeing traffic safety at minimal operational costs.Recieved 2025-11-07Recieved 2026-01-05Accepted 2026-02-11
Keywords: Street lighting system; multi-objective optimization; municipal systems; LED luminaires